Cry features of healthy neonates who passed their newborn hearing screening vs. those who did not. (May 2021) - Wermke, Kathleen; Cebulla, Mario; Salinger, Vivien; Ross, Veronique; Wirbelauer, Johannes; Shehata-Dieler, Wafaa
Abstract: Objectives: Temporal and fundamental frequency (fo) variations in infant cries provide critical insights into the maturity of vocal control and hearing performances. Earlier research has examined the use of vocalisation properties (in addition to hearing tests) to identify infants at risk of hearing impairment. The aim of this study was to determine whether such an approach could be suitable for neonates. Methods: To investigate this, we recruited 74 healthy neonates within their first week of life as our participants, assigning them to either a group that passed the ABR-based NHS (PG, N = 36) or a group that did not, but were diagnosed as normally hearing in follow-up check at 3 months of life, a so-called false-positive group (NPG, N = 36). Spontaneously uttered cries (N = 2330) were recorded and analysed quantitatively. The duration, minimum, maximum and mean fo, as well as two variability measures (fo range, fo sigma), were calculated for each cry utterance, averaged for individual neonates, and compared between the groups. Results: A multiple analysis of variance (MANOVA) revealed no significant effects . This confirms that cry features reflecting vocal control do not differ between healthy neonates with normal hearing, irrespective of the outcome of their initial NHS. Conclusions: Healthy neonates who do not pass the NHS but are normal hearing in the follow-up (false positive cases) have the same cry properties as those with normal hearing who do. This is an essential prerequisite to justify the research strategy of incorporating vocal analysis into NHS to complement ABR measures in identifying hearing-impaired newborns. Highlights: Utterance duration and fundamental frequency of spontaneous crying do not differ in healthy neonates who had different NHS outcome. Analysing neonatal crying could help to reduce false positive rate in NHS. Cry features could provide complementary information to early identify inborn hearing disorders.